Analysis of the state discourse before the IACHR (OAS): the case of Venezuela - González, Elienai (2021)
This article aims to elaborate an analysis of the official discourse in the thematic hearings held on February 27, 2018 before the Inter-American Commission on Human Rights (IACHR), in the city of Bogotá, Colombia, within the framework of the 167th period of sessions, pertaining to the Right to Food and Health, on the one hand, and to the National Constituent Assembly, on the other, which despite being two different issues, it is considered necessary to include both audiences in a single work to reflect the vision of the State in its entirety.  In this way, by reviewing the arguments of the Venezuelan authorities, from the perspective of national and international legal instruments, as well as institutional and journalistic sources, the factors that have contributed to the current complex situation will be systematically revealed and its implications for human rights.